An empirical analysis of correlation between the thickness of a thermal insulation layer of the floor and the payback period - Aviza, Donatas; Turskis, Zenonas (Journal of Civil Engineering and Management, 2014)
The article provides the correlation analysis between the thickness of a thermo-insulation layer of the typical floor-on-soil sample and its simple payback time in a traditional new construction single-apartment residential and net-zero energy building. The calculations were carried out on the energy efficiency class of the building and the geographic area of the construction. On the basis of the results, a simple payback time was calculated. The main aim – thermal transmittance coefficients of soil touching partitions must satisfy the normative value of technical construction regulation and European standards. The research object of the study is relationships between the thickness of a thermoinsulation layer of the typical floor-on-soil sample and its simple payback time. Lithuania was chosen as the geographic area of the research. Calculations were carried out for seven towns: Vilnius, Kaunas, Klaipeda, Siauliai, Panevezys, Utena, and Dukstas. The test result – developed correlation functions. Correlation analysis results are important not only for designers making decisions during the pre-design stage, but also for energy consumption auditors and experts.